Carbohydrate Content in Date Milk Juice (Phoenix dactylifera L.) to Facilitate Childbirth - Ulya, Yadul; Siskha Maya Herlina; Regina Pricilia Yunika; Dinda Rusti Pratama (Journal for Quality in Public Health, 2024)
Providing adequate nutrition is the main factor apart from other factors that supports a smooth delivery process. The nutritional needs of mothers in labor can be met by providing nutrition in the form of liquids that are easily digested and quickly absorbed into energy, delicious, practical, and suitable for the condition of the mother who is about to give birth. One way is to provide birth nutrition drinks in the form of juice. The aim of this research is to identify the carbohydrate content in date milk juice (phoenix dactylifera L.) as an alternative effort to fulfill the energy needs of mothers in labor to facilitate labor. The method used is descriptive quantitative with a laboratory experimental approach to determine the carbohydrate content in date milk juice. The results of the carbohydrate content test carried out showed that 100 ml of date milk juice had a carbohydrate content of 51.83% and the analysis of carbohydrate content used the luff schoorl method. It is hoped that the high carbohydrate content in 100 ml of date milk juice will provide energy and nutrition during labor so that it can help facilitate delivery.